Mechanisms for Implementing Administrative Judgments on the Environmental Right to Management - Ouadeh, Hamid; Djazoul, Salah (Journal of Legal Studies and Researches, 2023)
The State's direction in development through public administration has had a negative impact on the environment. Since the Constitution recognizes the human person's right to a healthy environment, the administrative judiciary has intervened by using its broad authority to issue executive orders and impose a fine on the administration under Law 08-09, to counter its failure or breach of its environmental rights obligations.